Maternal and Newborn Outcomes Among Women With Schizophrenia: A Retrospective Population-based Cohort Study. Issue 2 (June 2015) - Vigod, S.N.; Kurdyak, P.A.; Dennis, C.L.; Gruneir, A.; Newman, A.; Seeman, M.V.; Rochon, P.A.; Anderson, G.M.; Grigoriadis, S.; Ray, J.G.
Abstract : ( BJOG . 2014;121(5):566–574)